Preparation of rare earth oxides from Synchysite oxidized ore by acid leaching - J, Temuujin; G, Burmaa; B, Davaabal; Kim, D S; Lee, H J (Mongolian Journal of Chemistry, 2018)
Mixed rare earth oxides have been prepared from synchysite ore from the Lugiin gol rare earth deposit (Mongolia) which contains about 6% of cerium light rare earth elements. Ore powders were leached for up to 60 min using 80-120 g/l sulfuric acids at an acid to powder ratio of 20, agitation was performed by magnetic stirring followed by precipitation and calcination at 700°C for 1h. The highest leaching of REEs equal to 85% of the total REE was observed in the acid solution of 80 g/l. Obtained mixed rare earth oxides represent a layered type structure.